2000
DOI: 10.1074/jbc.m004373200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Mitogen-activated Protein Kinase Cascade and Tyrosine Phosphorylation of the Epidermal Growth Factor Receptor by Hepatopoietin

Abstract: Hepatopoietin (HPO) is a novel human hepatotrophic growth factor, which specifically stimulates proliferation of cultured primary hepatocytes in vitro and liver regeneration after liver partial hepatectomy in vivo. Recently, the identification of the mitogenic effect of HPO on hepatoma cell lines and the existence of HPO-specific receptors indicate that HPO acts via its specific cell surface receptor. However, the molecular mechanism of HPO action is not fully elucidated. In this report, we examined the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 20 publications
1
53
0
3
Order By: Relevance
“…Furthermore this isoform modulated hepatic detoxification by cross-linking growth signals to the regulation of hepatic metabolism (18). The proliferation augmenting effect of ALR was attributed to its ability to activate EGF receptor phosphorylation and the subsequent stimulation of the MAPK cascade (29). Furthermore, it has been elucidated that intracellular ALR may activate transcription factors via a MAPK independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore this isoform modulated hepatic detoxification by cross-linking growth signals to the regulation of hepatic metabolism (18). The proliferation augmenting effect of ALR was attributed to its ability to activate EGF receptor phosphorylation and the subsequent stimulation of the MAPK cascade (29). Furthermore, it has been elucidated that intracellular ALR may activate transcription factors via a MAPK independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999 we identified the existence of HPO-specific receptor on the surface of these cells (8). Furthermore, we proposed that extracellular HPO stimulates proliferation of hepatocytes and enhances liver regeneration by activating the MAPK signaling pathway under the mediation of HPO receptor (9). Intriguingly, we further found that intracellular HPO can specifically modulate the AP-1 pathway through JAB1 via a MAPK-independent pathway and that HPO enhances the increased phosphorylation level of cJun through JAB1 but has no effect on the expression of transfected c-Jun or endogenous c-Jun N-terminal kinase nor on phosphorylation of c-Jun N-terminal kinase (10).…”
Section: Hepatopoietin (Hpo)mentioning
confidence: 99%
“…Since LaBrecque et al (1) first reported hepatic stimulator substance in 1975, HPO has recently been the subject of intense investigation (2)(3)(4)(5)(6)(7)(8)(9)(10). Recombinant HPO can stimulate proliferation of hepatocytes as well as hepatoma cells in vitro, promote liver regeneration and recovery of damaged hepatocytes, and rescue acute hepatic failure in vivo (6,7).…”
Section: Hepatopoietin (Hpo)mentioning
confidence: 99%
“…Wang és munkatársai a "rövid" formájú (15 kDa) humán rekombináns rhALR magas affi nitású receptorait fedezték fel mind patkány-, mind humán hepatocytákon [34]. Az ALR receptorához történő kötése az EGFR foszforilá-cióját váltja ki, amely ezután a MAPK (mitogen-activated protein kinase) jelátviteli kaszkád aktiválódását okozza, amely fontos szerepet tölt be a sejtnövekedés szabályozásában [35]. Ezenkívül az ALR az EGFR-től független módon, az ERK1/2 (extracellular signal-regulated kinase 1/2) kinázok indukálásával is képes bekapcsolódni a MAPK-útvonalba [36].…”
Section: Az Alr Szerepe a Májregenerációbanunclassified